Satellite radio navigation system integrity control method with kalman filters group - Ковалевський, Е.О.; Куценко, О.В. (Proceedings of National Aviation University, 2010)
One of navigation satellite system integrity control method has been studied in this research. Modification of this method has been proposed. Modification has been explored by mathematic simulation.